Pengaruh Penggunaan E-Commerce Dan Kualitas Produk Terhadap Keputusan Pembelian Di Marketplace Akan Produk-Produk Busana (Studi Kasus Mahasiswa Program Studi Manajemen UNISKA) - Devano Empathanussa; Iing Sri Hardiningrum (Universitas 45 Surabaya, 2023)
This research aims to understand the impact of e-commerce use, and product quality on purchasing decisions in the marketplace of fashion products. (studi kasus mahasiswa program studi Manajemen UNISKA). The location of this research was carried out at Kadiri Islamic University, a college managed by the Pancasila Muslim Cendikia Foundation (YBCMP) located in Jl. The Sergeant No. 38, Manisrenggo, the town of Kediri, the district of Sediri. This research is quantitative. Data collection is done using methods of interviews, observations, documentation, and questionnaires. Data analysis is carried out using validity test methods, reliability test, classical assumption test that includes normality test, linearity test, multicolinearity trial, and heterocedasty test, double linear regression test, determination coefficient test, t test, and F test. The results of research have shown that there is a strong relationship between the variables of e-commerce, and the quality of the product to the purchase decision on the marketplace of fashion products. This is demonstrated by the R Square value of 0.815 so the correlation coefficient (relation) can be said to be very strong with the consumer prescription in deciding on the purchase in the marketplace of fashion products. (case study student’s Management Program of UNISKA).